Estabilidade da fixação antirrotacional lateral com parafuso associada à técnica de avanço de tuberosidade da tíbia - Chung, Denise Granato [UNESP] (2014)
The cranial cruciate ligament ( RLCCr ) is a common orthopedic disorder in dogs that promotes instability of the knee joint , resulting in lameness and progressive degenerative changes of the joint. Among the techniques for correction of the disease described in the literature, the success rate varies from 80-90 % and all have advantages and disadvantages. The objective of this project is to compare through biomechanical technique of tibial tuberosity advancement (TTA) and its association with anti-rotational lateral suture with nylon 1.0 mm fixed with surgical steel screw modified (TTAs). Ten hind limbs of dogs come from cadavers, which were submitted to two biomechanical tests at four different times were used. The tests were performed with the machine tests EMIC® DL 10000, and first test mimicked that of cranial displacement of the tibia relative to the femur (cranial drawer motion) and by the internal rotation of the tibia relative to the femur. The results showed that MT1 and MT4 Moments present similar values, 33.43 ± 5.25 and 29.71 ± 8.48 N/mm respectively, and higher than other times. And the test of rotation MR4 found average stiffness value of 9.95 ± 9.12 N/mm, which is different from other groups. By presenting the results that anti-rotational suture TTA was able to stiffen the knee. However, there were some limitations in the development of the study added to the sparse literature on the rotation, which suggests new research on the subject